1996
DOI: 10.1016/0370-2693(96)00276-6
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-quark production in eγ scattering

Abstract: Open heavy flavour production at e + e − colliders in deeply inelastic eγ scattering has an interesting feature: the structure function F 2 (x, Q 2 ) for this process is calculable for x > 0.01, and is essentially proportional to the gluon density in the photon for smaller x values. We give estimates for event rates at LEP2 and a Next Linear Collider in x, Q 2 bins, and present differential distributions in the transverse momentum and rapidity of the heavy quark for the case of charm. We include all next-to-le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…We would like, however, to point out that LEP2 offers the possibility of studying heavy-flavour production in photon-photon collisions. Relevant NLO computations have been performed for both the γγ [Drees93, Kraemer96] and the eγ cases [Laenen96]. Some phenomenological studies have already begun [Aurenche96].…”
Section: Preliminariesmentioning
confidence: 99%
“…We would like, however, to point out that LEP2 offers the possibility of studying heavy-flavour production in photon-photon collisions. Relevant NLO computations have been performed for both the γγ [Drees93, Kraemer96] and the eγ cases [Laenen96]. Some phenomenological studies have already begun [Aurenche96].…”
Section: Preliminariesmentioning
confidence: 99%
“…For real photons these cross sections are known up to NLO and can be found in [29]. In [30] it was shown that the two contributions are separated in the variable x: for large x, say, x 0.05, the direct process dominates, whereas for x 0.01 the dominant contribution stems from the resolved part.…”
Section: Treatment Of Heavy Flavorsmentioning
confidence: 99%
“…In each case this is motivated by the observation that all relevant fully massive production mechanisms appear to be perturbatively stable, at least for all experimentally relevant values of x and Q 2 (see, e.g., Refs. [21,30]). Moreover, all theoretical uncertainties, in particular the dependence on the factorization scale appear to be well under control, leading to the conclusion that there is no real need for any resummation procedure.…”
Section: Treatment Of Heavy Flavorsmentioning
confidence: 99%
“…[14], heavy quark production in two photon processes at an e + e − collider is discussed; although some mention is made of the heavy quark content of the photon, the bulk of the analysis deals with the production of heavy quark pairs via γγ, γg and gg fusion. Finally, Laenen and Riemersma [15] present a calculation of heavy quark production in eγ collisions using a fixed flavor scheme; as we consider the heavy quark as being a constituent of the photon, our approach should be considered to be complementary to that of Ref. [15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Laenen and Riemersma [15] present a calculation of heavy quark production in eγ collisions using a fixed flavor scheme; as we consider the heavy quark as being a constituent of the photon, our approach should be considered to be complementary to that of Ref. [15].…”
Section: Introductionmentioning
confidence: 99%